Collective capabilities in social innovations in the light of the 5C Cycle: An analysis of the Paraibana Network of Community Banks - Batista, Leonardo Ferreira; Correia, Suzanne Érica Nóbrega (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This article aims to empirically analyze the representation variables of the 5C Cycle of developing collective capabilities in social innovations: Capital, Conscientization, Conciliation, Collaboration, and Confluence. It brings relevance to studies in the area, as well as a contribution to strategies that develop collective capabilities in social initiatives. A study of the multiple cases of the Paraibana Network of Community Development Banks was constructed. It became evident that the use of capital and confluence practices are reflected mainly in the diffusion of practices of the initiatives. It is concluded, from a collective capabilities perspective, that the analysis of this framework in real contexts subsidizes collective capability development practices and promotes improved management of social innovation initiatives and the consequent local development.